Protection of Consumer Privacy in the Use of Big Data in the Digital Economy - Irwansyah, Irwansyah; Sari, Romida Rifiana; Hasanuddin, Hasanuddin; Rumianti, Susti (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research aims to see the extent of use of Big Data technology in Indonesia, both by government and private institutions, the challenges faced in its implementation, and its impact on consumer privacy. The research method used is a literature study with a traditional-conceptual approach. The main data sources are published journals related to the topic being studied and several reports from social media. In conclusion, the use of Big Data in Indonesia has begun to develop both in the business and public sectors. The current challenge is how companies can optimize the data they have, and regarding privacy violations, legal certainty and an understanding of ethics in the use of information technology are needed.   Keywords: Big data, digital economy, traditional-conceptual, consumer protection